1999
DOI: 10.1044/jslhr.4205.1176
|View full text |Cite
|
Sign up to set email alerts
|

Voice and Speech Characteristics of Persons With Parkinson’s Disease Pre- and Post-Pallidotomy Surgery

Abstract: Pallidotomy surgery, lesioning the globus pallidus internal, has been performed to alleviate Parkinsonian symptoms and drug-induced dyskinesias. Improvements in limb motor function have been reported in recent years following pallidotomy surgery. The purpose of this preliminary study was to determine the effect of pallidotomy surgery on select voice and speech characteristics of 6 patients with Parkinson's disease. Acoustic measures were analyzed pre-pallidotomy surgery and again at 3 months following surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 45 publications
2
25
0
1
Order By: Relevance
“…However, this study did not show evidence of changes in the usual frequency range, which is similar to the study of Ramig et al 19 . In the studied periods, it was observed an increase in F0 as Schulz et al 8 that observed an increase in the fundamental frequency in three out of six cases evaluated.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…However, this study did not show evidence of changes in the usual frequency range, which is similar to the study of Ramig et al 19 . In the studied periods, it was observed an increase in F0 as Schulz et al 8 that observed an increase in the fundamental frequency in three out of six cases evaluated.…”
Section: Discussionsupporting
confidence: 56%
“…There is an intimate relationship between F0 and vocal intensity; although increases in intensity are measured by greater glottal coaptation and activity of the respiratory mechanism, variations in intensity are dependent on the frequency and vice-versa. Regarding the evaluation of vocal intensity, some studies described a reduction in loudness after PVP 5,8,15, while Laitinen et al 6 observed an increase. Schulz et al 8 did not observe a correlation between the increase of F0 and the increase in vocal intensity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The "Deep Brain Stimulation", whose goal is to reduce the activities of the globus pallidus, subthalamic nucleus and thalamus, is a great promise for these patients 38 . Postoperative results have been very promising with important voice improvements, showing the way to a new therapeutic horizon [39][40][41][42] . However, we have to take into account that this technology is not available to most of these patients, especially in a developing country like Brazil, thus the importance of developing innovative and accessible approaches that help in assessing and treating vocal symptoms in this group.…”
Section: Final Remarksmentioning
confidence: 99%